THE EFFECTIVENESS OF GIVING NIGELLA SATIVA OIL TO SKIN INTERGITY DISORDERS IN ADOLESCENTS SUFFERS ACNE VULGARIS - Nunik Purwanti; Fitriasari, Andikawati (Universitas Nahdlatul Ulama Surabaya, 2022)
Introduction: Changing cosmetics can cause acne vulgaris. Objective: The research objective was to analyze the effectiveness of Nigella Sativa oil administration on skin integrity problems in adolescents with acne vulgaris in Kedensari Village RT 17 RW 05 Tanggulangin Sidoarjo. Methods: This study used Quasi Experimental with a pre-posttest control group design approach. The study population was all adolescents with acne vulgaris who experienced skin integrity problems in Kedensari Village RT 17 RW 05 Tanggulangin Sidoarjo. The sample was selected using the simple random sampling technique of 28 adolescents who were then divided into two groups, namely the experimental group of 14 people and the control group of 14 people. The independent variable was the administration of Nigella Sativa oil, while the dependent variable was the degree of skin integrity disorders in adolescents with acne vulgaris. The research instrument was a skin condition observation sheet. Data analysis used the Wilcoxon test and the Mann Whitney test with a significance value of α = 0.05. Results: The results showed: 1) There were significant differences in skin integrity before and after intervention in the intervention group p =0,001,(0,001<0,05) There were significant differences in skin integrity in the intervention group and the control group (p =0,000 <0.005). Conclusions: Giving nigella sativa oil is effective in improving skin integrity problems in adolescent with acne vulgaris. It is hoped that the nurses can use nigella sativa oil in providing care for adolescents with acne vulgaris.